2022
DOI: 10.1111/tbed.14712
|View full text |Cite
|
Sign up to set email alerts
|

Full genome characterization of a human‐porcine reassortment G12P[7] rotavirus and its pathogenicity in piglets

Abstract: In recent years, increasing numbers of cases of acute gastroenteritis caused by Group A rotavirus (RVA) G12 strains have been reported in humans from many countries around the world, but G12 RVA detection in animals is currently less reported. Pigs are an important animal reservoir of zoonotic RVs and a mixing vessel for RVs. In 2020, RVA infection cases in piglets increased in China, which attracted more attention. During an epidemiological survey, a new type of porcine G12P[7] strain (CN127) was detected in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 55 publications
0
11
0
Order By: Relevance
“…In a previous study, diarrhea was reported in piglets infected with PRG942 (G9P [23]) and PRG9121 (G9P [7]) strains at 1-8 dpi [42]. Furthermore, Miao et al reported diarrhea in 1-day-old piglets infected with the CN127 strain after 6-24 h, which continued until euthanization at 48 h, but none of them died due to the infection [38].…”
Section: Discussionmentioning
confidence: 94%
“…In a previous study, diarrhea was reported in piglets infected with PRG942 (G9P [23]) and PRG9121 (G9P [7]) strains at 1-8 dpi [42]. Furthermore, Miao et al reported diarrhea in 1-day-old piglets infected with the CN127 strain after 6-24 h, which continued until euthanization at 48 h, but none of them died due to the infection [38].…”
Section: Discussionmentioning
confidence: 94%
“…More and more evidence shows that RVA belonging to G9 and G12 genotypes was detected in the lungs and nasal swabs associated with lung damage ( 10 ). To some extent, these studies indicated that (1) the respiratory transmission route was another route of RV transmission, (2) the lungs could be another target for RV infection, and (3) nasal swabs or lung samples should be considered candidate samples for the detection of RV.…”
Section: Discussionmentioning
confidence: 99%
“…PoRVs are prevalent worldwide and result in significant economic losses to the swine industry [ 15 ]. Isolation and cell-based cultivation of PoRV can help understand their pathogenicity in piglets [ 38 ]. In this study, PoRV-positive samples from a pig farm, suffering from diarrhea in suckling piglets, were treated with 10 µg/mL trypsin for 1 h, and the optimal conditions for the isolation of PoRV were established by adding trypsin to a final concentration of 4 µg/mL in the maintenance medium.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, diarrhea was reported in piglets infected with PRG942 (G9P[23]) and PRG9121 (G9P[7]) strains at 1–8 dpi [ 42 ]. Furthermore, Miao et al reported diarrhea in 1-day-old piglets infected with the CN127 strain after 6–24 h, which continued until euthanization at 48 h, but none of them died due to the infection [ 38 ].…”
Section: Discussionmentioning
confidence: 99%